Exploring ChatGPT as an AI-Powered Feedback Tool in EFL Writing: A Systematic Literature Review - Sardi, Ahmed; Dollah, Syarifuddin; Abdullah, Abdullah (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2026)
EFL writing presents challenges not only for students but also for teachers who must provide constructive feedback to promote student improvement. Given the substantial workload that teachers often face, there is a growing need for tools that can support the feedback process. The rise of Artificial Intelligence (AI), particularly tools like ChatGPT, has introduced new opportunities in the field of education. Its potential to assist in providing feedback has garnered significant attention. Several studies have explored students’ perceptions of receiving feedback through ChatGPT in EFL writing, with findings that vary in scope and sentiment. This study aims to explore students’ general perceptions of ChatGPT as a feedback tool, examining both its benefits and drawbacks as reported in the existing literature. Using the PRISMA Systematic Literature Review model, this research analyzes five out of 29 articles that met the inclusion criteria established for the review. The findings suggest that, in general, students have a positive perception of ChatGPT as a feedback provider. However, the data also indicate that ChatGPT cannot fully replace human feedback, such as that provided by teachers, due to the various advantages and limitations of the tool. These insights can serve as valuable guidance for teachers who are considering incorporating ChatGPT into their feedback practices for EFL writing. By understanding both the potential and the challenges of AI-driven feedback, teachers can make informed decisions on how best to support their students' writing development.